Three-dimensional visualization of brain tumor computed tomography images / Nurizzaty Khairi Mohamed - Nurizzaty Khairi, Mohamed (2021)
Open-source software used to reconstruct and visualize 3D image from 2D computed tomography (CT) images. This research used Visualization toolkit (VTK) and 3D slicer software to reconstruct 3D image from a set of 2D brain tumor CT image. Each software practiced four different methods to visualize 3D image from a set of 2D image. Methods used in VTK software are surface rendering, multiplanar rendering, volume rendering and volume rendering with additional features while 3D slicer software display surface of 3D model, multiplanar 3D model, volume 3D model and volume with measurement 3D model. A set of 2D brain segment images obtained from CT scan used as source data. The reconstructed 3D images expected to visualize 2D brain tumor CT images into 3D image and measure 3D volume of brain tumor. Result of 3D slicer will be used for comparison purposes. The result shows that both software capable to reconstruct and visualize 3D image from a set of 2D images. However, volume rendering with additional features method by using VTK shows the best result in reconstructing 3D image from a set of 2D images because of lower noise and artifacts present in the 3D image. Plus, the method able to crop the 3D image and allow user to observe cross-section of the 3D image for measuring the brain tumor size. In conclusion, 3D reconstruction software ease physicians and radiologists to diagnose abnormalities faster and precisely.